PENGARUH ISLAMIC ATTRIBUTES, DESTINATION ATTRIBUTES DAN QUALITY OF SERVICE TERHADAP ISLAMIC TOURISM SATISFACTION PANTAI TIRAM PARIAMAN - Muhammad Luthfi; Irda Irda; Reni Yuliviona (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
This study aims to determine the effect of Islamic Attributes, Destination Attributes and Quality of Service on Islamic Tourism Satisfaction Tiram Beach in Pariaman. This is phenomenon of seasonal tourist visits to the tourist area Tiram Beach. The sample in this study was tourists who traveled in the tourist area of Tiram Beach in Pariaman totaling eighty respondents. The sampling technique is purposive sampling. The type of data in this study are primary data from questionnaires. The data analysis method in this study was Smart PLS analysis. Hypothesis testing using the R-Square test to see the results of the influence of independent variables on the dependent variable. The results of this study found that the Islamic Attitude and Destination Attributes had a significant effect and Quality of Service did not significantly influence tourist satisfaction